1982
DOI: 10.2527/jas1982.5461212x
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin and Luteinizing Hormone Secretion after Bromocryptine (CB-154) Treatment in Lactating Sows and Ovariectomized Gilts1

Abstract: The effects of bromocryptine (CB-154) on prolactin (PRL) and luteinizing hormone (LH) secretion were studied in lactating sows and ovariectomized (OVX) gilts. In Exp]. 1, the litters of four sows were standardized to four pigs each at 20 to 30 d of lactation and a cannula was placed nonsurgically into the jugular vein of each sow. Twenty-four hours later (0800 h) blood samples were taken and two sows each were injected subcutaneously with 120 mg CB-154 or vehicle. Blood samples were then taken every 30 min for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(36 citation statements)
references
References 17 publications
1
35
0
Order By: Relevance
“…The role of dopamine was first investigated in lactating sows by using a short-acting agonist, bromocryptine. The agonist induced either a decrease [32] or an increase [33] in LH secretion during the third week of lactation. In 1998, De Rensis et al [34] reported that the administration of a long-acting dopamine agonist, cabergoline, increased LH secretion in late lactation.…”
Section: Discussionmentioning
confidence: 99%
“…The role of dopamine was first investigated in lactating sows by using a short-acting agonist, bromocryptine. The agonist induced either a decrease [32] or an increase [33] in LH secretion during the third week of lactation. In 1998, De Rensis et al [34] reported that the administration of a long-acting dopamine agonist, cabergoline, increased LH secretion in late lactation.…”
Section: Discussionmentioning
confidence: 99%
“…Intra-assay CV was 16.4%. Concentrations of PRL were quantified according to validated procedures (15). Intra-assay CV was 13.8%.…”
Section: Introductionmentioning
confidence: 99%
“…Porcine FSH TUSDA-pFSH-PPIB) was used as radioiodinated i'"1; antigen (see Kraeling et al 1982) and USDA-pFSH-B- Rawlings et al (19"1'7, 1980) using an antiserum raised against 4-Pregnen-1 1a-o1-3,20-dione hemisuccinate:BSA (N. C. Rawlings, University of Saskatchewan, Saskatoon). Assay sensitivity was 0.05 ng per tube.…”
mentioning
confidence: 99%